INCREASING THE STUDENT’S SPEAKING SKILL IN DESCRIBING THINGS BY USING YOUTUBE VIDEO AT THE ELEVENTH GRADE OF SMA NEGERI 3 MANDREHE UTARA IN 2022/2023 - Gulo, Sastrawan; Laoli, Adieli; Harefa, Afore Tahir; Zebua, Elwin Piarawan (Dharmas Education Journal (DE_Journal), 2023)
Speaking is a way of communicating with the other people orally. In fact, there was a gap between the expectations and the reality. The students were unable to speak the describing things by using YouTube video. The objective of the research is to increase the students’ speaking skill in describing things by using YouTube video. This research applied Classroom Action Research in order to improve students’ speaking ability in describing things. The subject of the research were students at at the eleventh grade of SMA Negeri 3 Mandrehe Utara consist of 20 students. The instruments to collecting the data were observation, evaluation, and field notes. The result in this research showed that there were enhancement of students’ speaking skill in describing things. In Cycle I the students failed to achieve the MCC and the average of the student’s scores was 55, the average of fluency level score in cycle I was 2+. But in Cycle II the students were successful, the average of the students’ score was 75, the average of fluency level score in cycle I was 3+. Because of students’ grades in cycle II is higher than cycle I, the researcher concludes that YouTube video can increase the students speaking skills in in describing things at the eleventh grade of SMA Negeri 3 Mandrehe Utara.